A Density Functional Theory Study on Paracetamol-Oxalic Acid Co-Crystal - Paudel, Punya; Adhikari, Kapil (Himalayan Physics, 2020)
Paracetamol (PCA) has two well-known polymorphic forms, monoclinic (form I) and orthorhombic (form II). The parallel packing of ﬂat hydrogen bonded layers in the metastable form II results in compaction properties superior to the thermodynamic stable form I which contains corrugated hydrogen bonded layers of molecules. In this study, the structure of Paracetamol (PCA)-Oxalic acid (OXA) co-crystal has been analyzed and found layered structure similar to PCA form II which enhance ability to form tablet. The Density Functional Theory (DFT) has been conducted to ﬁnd some physicochemical properties of co-crystal. It was observed that the lattice energy of co-crystal is more than that of PCA form II showing more stability on co-crystal. The energy gap between highest occupied molecular orbital and lowest unoccupied molecular orbital (HOMO-LUMO gap) in co-crystal was found less than PCA form II showing bigger enhancement of reactivity.